Politika prejemkov organov vodenja in nadzora - de lege lata in uskladitev z direktivo o sodelovanju delničarjev - Strojin Štampar, Anja (Podjetje in delo, 2018)
Remuneration is one of the key instruments for shareholders to align their interests and those of their directors. Over the last two decades, the discussion on the remuneration has been focused primarily on the appropriateness of remuneration policies in the listed companies, and on the role of shareholders in the determination of remuneration policy (say-on-pay initiatives). To this end, numerous law amendments and best practice recommendations have been adopted. The latest legal act in this field is the Shareholders' Rights Directive II, which provides for a more detailed disclosure of directors' remuneration and strengthens the role of shareholders in determining remuneration policies, either through a binding or an advisory vote on the remuneration policy, which should be based on a clear, understandable and comprehensive overview of the company's remuneration policy. The remuneration policy should be determined in such a way that it contributes to the business strategy, long-term interests and sustainability of the company, and should not be linked entirely or mainly to short-term objectives. The article summarises the current remuneration regulation and say-on-pay rights in Slovenia. The Slovenian legislation should be harmonised with the Directive by June 2019.
Keywords: delničarska direktiva; fiksni in variabilni prejemek; organi nadzora; organi vodenja; politika prejemkov; razkritja prejemkov